After postmodernism: "descendants" / "masks"? (philosophical sketch) - Kutsepal, Svitlana (Actual Problems of Mind, 2021)
The article reveals a range of different versions of the discourse of postmodernism, which seek to describe the social and cultural component of the world of the third millennium, but rejecting the philosophical pathos of postmodernism, only confirm its viability. History repeats itself, because postmodernism emerged in the realm of modernism, manifesting a rejection of universals, narratives and grand narratives, abandoning the focus on European scale and priority, fascinated by the phenomenon of consumption, Americanization and Westernization. The postmodernism’s ontico-ontological background was presented by the element of decentralization, generated by ontological and epistemic doubts, «dispersed perception», caused by acquaintance and fascination with the creative possibilities of chaos. The progressive postmodern thesis about the balance of any discourses influenced the legitimation of differences, the recognition of marginalized groups and strata of society, the reconsideration of attitudes towards race, sex, gender, etc. The rebellious pathos of postmodernism is that this intellectual phenomenon positioned itself not only as a certain set of ideas, but also as a historical dimension of the epoch, the essence of which had to be revealed. The variability of postmodern concepts is united by the pathos of denial, the rejection of the achievements of predecessors, the belief in the truth of only one’s own position. This is a purely postmodernist approach, described in detail by J.-F. Lyotard in his work «Differend: Phrases in Dispute» (1998). All postmodern theoretical constructions, in contrast to the postmodern, do not focus only on criticism and deconstruction, but seek to find and predict trends in society in the XXI century, but focus mainly on the cultural component, ignoring politics and economics. Therefore, all new «trends» are only «simulacra» of postmodernism, because they cannot adequately describe the current state of society, so postmodernism remains relevant in the XXI century.